Supporting elite athletes in a new age: experiences of personal excellence advisers within Australia`s high-performance sporting environment - Chambers, T. P.; Harangozo, G.; Mallett, C. J. (Qualitative Research in Sport, Exercise and Health, 2019)
Traditional career assistance programs focused on the provision of vocational and educational support for elite athletes. Following a recent shift towards the provision of holistic support services for these athletes, the purpose of this research was to explore the newly developed Personal Excellence (PE) adviser role within Australia`s high-performance sport system. The current investigation was exploratory in nature and examined the PE role, adviser experiences and essential services provided by these advisers in supporting Australia`s elite athletes. Utilising an interpretative phenomenological analysis (IPA), six individuals (Mage = 47.0, SD = 28.6) who were employed in a PE position within Australia`s National Institute Network participated in this study. In analysing the data according to IPA guidelines, six superordinate themes were identified: a) rationale for change; (b) program architecture; (c) essential services; (d) fundamental skills and qualities; (e) limiting factors; and (f) future opportunities. Consistent with IPA conventions, a thematic map was generated to illustrate the relationship between these factors. As the first empirical study of the PE program, this paper makes a valuable contribution to understanding the role of support programs in the elite sporting landscape and enhances the growing evidence-base on the provision of career assistance and wellbeing programs for elite athletes.